Evolution of the ion environment of comet 67P/Churyumov-Gerasimenko - Observations between 3.6 and 2.0 AU - Nilsson,H; Wieser,GS; Behar,E; Wedlund,CS; Kallio,E; Gunell,H; Edberg,NJT; Eriksson,AI; Yamauchi,M; Koenders,C; Wieser,M; Lundin,R; et al. (Astronomy & Astrophysics, 2015)
Context. The Rosetta spacecraft is escorting comet 67P/Churyumov-Gerasimenko from a heliocentric distance of >3.6 AU, wherethe comet activity was low, until perihelion at 1.24 AU. Initially, the solar wind permeates the thin comet atmosphere formed fromsublimation.Aims. Using the Rosetta Plasma Consortium Ion Composition Analyzer (RPC-ICA), we study the gradual evolution of the comet ionenvironment, from the first detectable traces of water ions to the stage where cometary water ions accelerated to about 1 keV energyare abundant. We compare ion fluxes of solar wind and cometary origin.Methods. RPC-ICA is an ion mass spectrometer measuring ions of solar wind and cometary origins in the 10 eV–40 keV energyrange.Results. We show how the flux of accelerated water ions with energies above 120 eV increases between 3.6 and 2.0 AU. The 24 haverage increases by 4 orders of magnitude, mainly because high-flux periods become more common. The water ion energy spectraalso become broader with time. This may indicate a larger and more uniform source region. At 2.0 AU the accelerated water ion fluxis frequently of the same order as the solar wind proton flux. Water ions of 120 eV–few keV energy may thus constitute a significantpart of the ions sputtering the nucleus surface. The ion density and mass in the comet vicinity is dominated by ions of cometary origin.The solar wind is deflected and the energy spectra broadened compared to an undisturbed solar wind.Conclusions. The flux of accelerated water ions moving from the upstream direction back toward the nucleus is a strongly nonlinearfunction of the heliocentric distance.